LbNR-Derived Nitric Oxide Delays Lycium Fruit Coloration by Transcriptionally Modifying Flavonoid Biosynthetic Pathway - Li, Gen; Qin, Beibei; Li, Shuodan; Yin, Yue; Zhao, JIan h.; An, Wei; Cao, Youlong; Mu, Zixin (Frontiers in Plant Science, 2020)
Anthocyanins-derived fleshy fruits pigmentation has become an excellent system for studying the regulatory network underlying fruit ripening and quality. The transcriptional control of anthocyanin biosynthesis by MYB-bHLH-WDR complexes has been well estalished, but the intermediate signals through which the environmental or developmental cues regulate these transcription factors remains poorly understood. Here we found that nitric oxide (NO) production during Lycium fruit ripening decreased progressively presenting a negative relationship with anthocyanins. After cloning of the nitric reductase (NR) gene from Lycium barbarum (LbNR) plants, we demonstrated that LbNR-derived NO partially inhibited anthocyanin biosynthesis but enhanced proanthocyanidins (PA) accumulation, and delayed fruit coloration. Application of the NO donor, sodium nitroprusside (SNP), produced a similar effect. The endogenous or exogenous NO down-regulated the transcripts both of the regulatory genes and the structural genes that related to anthocyanin biosynthesis, while up-regulated both of those genes that related to PA biosynthesis. Given there is a significant negative relationship between the levels of anthocyanins and PAs during Lycium fruit ripening, NO not only inhibited anthocyanin de novo biosynthesis but redirected the flavonoid biosynthetic pathway from anthocyanins to PAs production. Two types of LrMYB transcription factors of opposite nature, namely anthocyanins-specific and PAs-specific, which belonging to R2R3-MYB subfamily and 1R-MYB subfamily, respectively, were identified from L. ruthenicum fruits. It was further found that NO acts by antagonizing the ABA signaling, a phytohormone we have previously shown playing a positive role in Lycium fruit coloration. Our results provided particularly novel information about NO-ABA-anthocyanin interplay during Lycium fruit development and ripening, which may fill a gap between the developmental cues and the transcriptional regulation of anthocyanin biosynthesis.